Relaminarization of jet impingement on a flat plate using separation-induced transition correction turbulence modeling preliminarily applied in archeological applications - Mongkol Kaewbumrung; Chalermpol Plengsa-Ard (Heliyon, 2024)
The focus of the study was the validation of transition flow model which works with jet impingement applications. Reynolds averaged Navier Stokes (RANS) techniques, including a variation of transition options, such as γ−GEKO−k−ω, γ−SST−k−ω, transition SST and transition k−kl−ω, were employed to simulate the turbulent flow fields. ANSYS-Fluent 2022R2 was the tool used in the study and a constant surface heat flux on a flat plate was chosen for the test case. The flow characteristics and averaged Nusselt number prediction were investigated and compared with measurement data. The results show that the collapse of turbulence performed the flow became lamina-like in the transition region, 1 < r/D < 3, while the shape of velocity distribution within that region was parabolic profiles near a target wall. That means the relaminarization mechanism was captured by the transition SST model. Moreover, the thermal results demonstrated that the highest values of the Nusselt number prediction were located near the stagnation point and decreased monotonically within the wall jet regions. The predicted results from γ−SSTk−ω and transition SST models provided strong agreement with experimental data. Secondary peaks of the Nusselt number in the radial direction were also depicted by transition SST models, and these second peaks were still aligned on the ratio (1 ≤ r/D ≤ 3) which was not impacted by jet diameter variation. This range will be used in the next step of developing a prototype of a dehumidifying unit for use in archeological applications.